Pengaruh Pengetahuan Investasi Terhadap Minat Mahasiswa Untuk Berinvestasi Saham Di Pasar Modal - Hendra Arjuna; Defrizal ,; Habbiburahmman . (Peneliti.net, 2023)
Investors in the Indonesian capital market continue to increase in number every year. The current total capital market investors are 6,100,525 investors. But this number is still very far when compared to the total population of Indonesia. What is the strategy of stakeholders in the Indonesian capital market to increase student interest in investing in shares in the capital market. This study aims to determine and examine how influential investment knowledge is on the interest of students from the Faculty of Economics and Business at Bandar Lampung University batch 2018 to invest in stocks in the capital market.The population in this study were regular undergraduate students/class 2018 Faculty of Economics and Business, University of Bandar Lampung with a total of 211 people. In this study, the determination of the sample using random sampling technique (random). And for the data collection technique using a questionnaire (google form) which will be distributed to regular S-1 students/I class 2018 Faculty of Economics and Business, University of Bandar Lampung.It is known that based on the results of research, investment knowledge has a positive and significant effect on the investment interest of FEB students at Bandar Lampung University batch 2018, with a tcount value of 10,560 > from ttable 2,008. The average of the 18th FEB UBL students' answers regarding investment knowledge and investment interest are in the